Analisis Kepatuhan Syariah dalam Implementasi Akad Murabahah pada Produk Pembiayaan Emas (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the rapid development of Islamic Microfinance Institutions (LKMS) which play an important role in supporting the economy of small and medium-sized communities through the provision of financing products based on sharia principles. One of the dominant contracts used is murabahah, especially in gold financng products. However, in practice there are still problems related to the gold delivery mechanism and full compliance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This study aims to assess the implementation of the murabahah contract in gold financing products at LKMS MM Sejahtera, Bengkulu Province, with a focus on its compliance with sharia principles and the DSN fatwa. The research method used is field research with a descriptive qualitative approach through in-depth interviews, direct observation, and documentation studies. The results show that LKMS MM Sejahtera develops sharia-based gold savings products by utilizing a combination of murabahah, wadi'ah, and istishna' contracts. Transactions are carried out transparently, with profit margins determined based on mutual agreement between the LKMS and customers. Furthermore, supervision by the Sharia Supervisory Board (SSB) is a crucial instrument in ensuring that every stage of the transaction complies with Sharia principles. This study's findings confirm that the gold financing scheme through the murabahah contract at MM Sejahtera Islamic Financial Institution (LKMS) allows the public to invest in gold gradually while maintaining Sharia compliance. Implementation in accordance with the DSN fatwa not only avoids potential gharar practices but also strengthens public trust in Sharia financing products, thereby encouraging the sustainable growth of LKMS.